2001
DOI: 10.1074/jbc.m011067200
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Evidence for Substrate-assisted Catalysis in a Bacterial β-Hexosaminidase

Abstract: Carbohydrates are involved in many diverse biological functions including cell structural integrity, energy storage, pathogen defense and invasion mechanisms, viral penetration, and cellular signaling. Therefore, a large number of enzymes dedicated to carbohydrate metabolism have evolved. Enzymes specifically responsible for carbohydrate catabolism are collectively referred to as glycosyl hydrolases and have been classified into 77 families based on amino acid sequence similarity (1-3). Three-dimensional struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
292
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 255 publications
(301 citation statements)
references
References 46 publications
9
292
0
Order By: Relevance
“…In family 18 chitinases, the proton donor residue has been shown to be a glutamate, whereas the residue that acts as the nucleophile has not been detected by either mutational or X-ray diffraction analyses [2][3][4], indicating that the reaction mechanism of family 18 chitinases differs from that of other retaining enzymes. Similar situations have also been observed with family 20 glycosidases (e.g., b-N-acetylhexosaminidase) and family 56 glycosidases (e.g., hyaluronidase) [5][6][7][8].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In family 18 chitinases, the proton donor residue has been shown to be a glutamate, whereas the residue that acts as the nucleophile has not been detected by either mutational or X-ray diffraction analyses [2][3][4], indicating that the reaction mechanism of family 18 chitinases differs from that of other retaining enzymes. Similar situations have also been observed with family 20 glycosidases (e.g., b-N-acetylhexosaminidase) and family 56 glycosidases (e.g., hyaluronidase) [5][6][7][8].…”
Section: Introductionsupporting
confidence: 79%
“…This is a strong support for the substrate assisted catalysis mechanism, because compound 4 was designed to reduce the polarization of the carbonyl (thionyl) group in order to weaken the nucleophilic effect of the oxygen (sulfur) atom. Furthermore, the 3D-structure of a family-20 b-N-acetylhexosaminidase from Streptomyces plicatus complexed with GlcNAc-thiazoline (8) suggested that the enzymatic hydrolysis proceeded via a cyclic intermediate [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…27 In order to locate the PYR ligand, a difference Fourier map was calculated with the Collaborative Computational Project 4 (CCP4) 28 suite of programs (S Fall , 29 Sigma-A, 30 and Refmac5 31 for rigid body refinement) using the PDB coordinates (1NOU) of the native β-hexosaminidase B. 1 PYR, sugars, SO 4 ions, and water molecules were not included in the initial rigid body refinement and map calculations but were added in subsequent rounds. Further rounds of refinement were also carried out with Refmac5.…”
Section: Data Collection and Refinementmentioning
confidence: 99%
“…All the members of this family use a substrate-assisted catalysis mechanism, which is achieved by positioning the C2-acetamido group of the terminal GalNAc into the appropriate position for nucleophilic attack of the carbonyl oxygen atom on C1. 4,5 The substrate binding environment also ensures that a β-configuration is retained by directing the position of the incoming nucleophilic water molecule. A detailed description of the catalytic mechanism can be found in the paper by Lemieux et al 6 Genetic defects in either gene encoding the subunits of HexA can result in the accumulation of G M2 ganglioside in neural tissues and two of three lysosomal storage diseases collectively known as G M2 gangliosidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although GH3 enzymes, including NagZ, are functionally related to the GH20 human b-hexosaminidase isoenzymes and GH84 O-GlcNAcase, recent kinetic [17][18][19] and structural studies 16,[20][21][22] have revealed that GH3 enzymes use a catalytic mechanism that differs from that used by GH20 and GH84 enzymes. This distinction should therefore offer a tractable route to generating selective inhibitors of NagZ, and clear comparisons of these enzymes at a structural level would greatly accelerate these efforts.…”
mentioning
confidence: 99%